Greater trochanteric osteotomy and subtrochanteric osteotomy in primary/revision total hip arthroplasty - Pan, Yuqi; Chen, Yunsu (Frontiers in Surgery, 2023)
Total hip arthroplasty (THA) is the most common and effective reconstructive hip procedure for end-stage hip diseases, such as hip osteoarthritis and avascular necrosis of the femoral head. Although THA can significantly improve function and reduce pains, revision hip surgery may be needed when complications arise, such as repeated dislocation of the implant, hip joint infection, peripheral joint osteolysis, and implant instability. Under some circumstances, osteotomy procedures of the femur are necessary regardless of the primary THA or revision THA. The osteotomy methods of the femur mainly include greater trochanteric osteotomy (including standard greater trochanteric osteotomy 、modified greater trochanteric osteotomy、trochanteric slide osteotomy、extended trochanteric osteotomy) and subtrochanteric osteotomy (including transverse、double-V、stepped subtrochanteric osteotomy). All osteotomy methods have their specific indications, while nonunion is an unavoidable problem for all osteotomy methods. In this paper, we analyzed the trochanteric osteotomy and the subtrochanteric methods in primary and revision THA and summarized the characteristics of different osteotomy methods.